Pendampingan Pengolahan Limbah Cair Jasa UMKM Laundry dan Jasa Cuci Mobil dan Motor di Wilayah Cimahi Utara Kota Cimahi - Yulianto, Bambang; Kahar, Kahar; Sudiapermana, Elih; Saepudin, Asep (Jurnal SOLMA, 2024)
Background: The management of liquid waste from public services such as laundry businesses, as well as car and motorcycle washing businesses in the Pasirkaliki Village area, North Cimahi District, Cimahi City, is still inadequate, this can be seen from the absence of treatment efforts in wastewater disposal. The goal is to carry out counseling activities and make activated carbon filters as a stimulant to reduce COD levels in liquid waste from the results of public service activities. Method: The partners of this activity are the laundry business group consisting of 5 units and the car and motorcycle washing business group consisting of 2 units located in the Pasirkaliki District, North Cimahi District, Cimahi City. Counseling activities were carried out by visiting each member of the business group, while the placement of activated carbon filters as stimulants was chosen from the laundry business group considering that the number of businesses was higher. Results: As a result of the application of activated carbon filters as a stimulant in the laundry business, there was a decrease in COD from 2650 mg/l to 90 mg/l so that it was safe to dispose of in water bodies. Conclusion: Laundry business owners and car and motorcycle wash business owners realize that the management of liquid waste resulting from this is marked by the formation of a laundry business community group chaired by laundry owners and car and motorcycle wash business community groups chaired by car and motorcycle.